Peralihan status sertifikat hak pakai BMD aset pemerintahan kota berubah menjadi sertifikat hak guna bangunan milik Mega Mall - Muhammad Abizar Nuroval; Muhammad Alvian Rhamadani; Faisah Akramadji; Muhammad Fadlie Ramadan; Dhafin Abillah Anrepa (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study examines in depth the mechanism of land legal status transfer from Right of Use in the name of the Bengkulu City Government to Building Use Rights (HGB) over Management Rights (HPL), as well as through other cooperation mechanisms implemented by the management of Mega Mall Bengkulu. This change in land status is a strategic legal instrument in optimizing Regional Property (BMD), with the aim of increasing Regional Original Income (PAD) and supporting economic and social development at the local level. This transfer of rights reflects how public assets can be utilized legally and commercially, without eliminating local government ownership of the land, while maintaining social functions and public interests. The research method used is normative juridical, with an approach of studying laws and regulations, legal document analysis, and case studies. This study focuses on the conformity of the procedure for the transfer of Right of Use to HGB with Government Regulation Number 27 of 2014 concerning Management of State/Regional Property, implementing regulations, and derivative regulations related to regional asset management and cooperation with the private sector. The analysis also emphasizes transparency, accountability, legal certainty, and post-transfer monitoring mechanisms to ensure the land continues to provide maximum benefits to local governments and the community. The results show that the transfer of rights from Right to Use of BMD to HGB does not eliminate city government ownership, but rather grants temporary use rights to private parties for a certain period. This transfer provides opportunities for local governments to optimally utilize public assets, but also poses challenges in terms of monitoring the validity period of rights, legal certainty when the contract expires, and protection of public interests. This study found that the success of the transfer of rights is highly dependent on transparency of cooperation agreements, fair asset valuation, and professional contract management. In addition, the study emphasizes the importance of social and environmental evaluations in the use of BMD for commercial purposes. Land management must consider the impact on the surrounding community, the social function of the land, and the balance between economic development and the public interest. The implementation of periodic monitoring mechanisms, monitoring the fulfillment of developer obligations, and determining socio-economic contributions and public facilities are important factors in maintaining the sustainability of land benefits for the community. This article concludes that the transfer of the Right to Use (Hak Pakai) from a BMD to a HGB (Hak Pakai) for Mega Mall Bengkulu is an effective strategy in public asset governance, with the caveat that the entire process must be carried out in accordance with the law, principles of transparency, and accountability. The success of this transfer is not only economically beneficial but also strengthens local government governance, safeguards public interests, and serves as a model for professional and sustainable regional asset management. Therefore, this transfer of rights can serve as an example for other local governments in maximizing the use of public assets for inclusive, efficient, and equitable urban development.